PEDOT: PSS composite deposited on a microplatinum electrode as a robust biosensor transducer for applications in liquid media - Benoudjit, Abdel Mohsen; Abdul Guthoos, Habibah Farhana; Arris, Farrah Aida; Wan Salim, Wan Wardatul Amani (IIUM, 2016)
Over the last few decades, electrochemical transducers based on conductive polymers have received considerable attention owing to their physical and chemical characteristics with a potential to enhance the performance of an electrochemical biosensor in liquid media. Simultaneous electropolymerization and deposition of 3,4-ethylenedioxythiophene and poly(styrene sulfonate) (EDOT and PSS) on a microplatinum electrode (μPtE) surface was performed. The surface area of the electrode was varied by changing the length: 10 mm and 5 mm with a fixed diameter of 50 μm. Electropolymerization of EDOT:PSS to poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) was conducted using galvanostatic mode in a potentiostat/galvanostat at 100 μA and 400 mV. The electrochemical measurements were performed in 0.1 M potassium ferrocyanide (K3Fe(CN)6) solution. Redox currents over 6 days were measured in terms of anodic peak current using cyclic voltammetry (CV). Field emission scanning electron microscope (FESEM) results revealed the effect of liquid media on PEDOT:PSS film deposited on a higher surface area before and after measurement. Although anodic peak current did not change significantly for electrode lengths of 10 mm and 5 mm (~0.20 mA) on day one, the stability of current measurements (anodic peak current at day six in comparison to day one) decreased by 20% and 85% for 10 and 5 mm electrode lengths, respectively. This study has found that PEDOT:PSS deposited on a 5-mm microplatinum electrode with non-uniform films lost measurement stability in terms of anodic peak current after one week. However, a 10-mm microplatinum electrode with better film uniformity was able to maintain measurement stability for 2 weeks. The results enable development of PEDOT:PSS as a transducer layer deposited on microplatinum wire with a micrometer (μm) diameter for producing a robust electrochemical biosensor for applications in liquid media.